IMPLEMETASI APTITUDE TREATMENT INTERACTION TERHADAP HASIL BELAJAR EDUCATIONAL STATISTICS MAHASISWA PENDIDIKAN BAHASA INGGRIS IKIP PGRI BOJONEGORO - Dian Ratna Puspananda (Journal of Mathematics Education and Science, 2019)
This study aims to determine the effectiveness of the Aptitude Treatment Interaction learning model on the learning achievement of English education students in the subject of educational statistics. The instrument used is a subjective test. The sample used was 50 students, 22 students in the control class, and 28 students in the experiment class of the English Education study program at the Faculty of Language and Art Education at IKIP PGRI Bojonegoro. The data analysis used in this study is a t-test. The results of the study showed that the learning achievement of students of the English language education program became better after being given Aptitude Treatment Interaction in the Educational Statistics course. Penelitian ini bertujuan untuk mengetahui keefektifan model pembelajaran Aptitude Treatment Interactionterhadap hasil belajar mahasiswa pendidikan bahasa inggris pada mata kuliah educational statistics. Instrumen yang digunakan adalah soal uraian. Sampel yang digunakan sebanyak 50 mahasiswa, 22 mahasiswa pada kelas kontrol dan 28 mahasiswa pada kelas eksperimen dari program studi Pendidikan Inggris Fakultas Pendidikan Bahasa dan Seni IKIP PGRI Bojonegoro. Analisis data yang digunakan dalam penelitian ini adalah t- test. Hasil penelitian menunjukkan bahwa hasil belajar mahasiswa program studi pendidikan bahasa inggris menjadi lebih baik setelah diberikan pembelajaran Aptitude Treatment Interaction pada mata kuliah Educational Statistics.